CELEBRITY ENDORSER, BRAND IMAGE, & KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - fasya, fasya (IAIN Langsa, 2017)
This research was aimed to find out how big the effect of celebrity endorser, brand image and customer satisfaction toward the customer loyalty both directly and indirectly influence. The sample used in this research were consumers who make purchases in the shopping centre in Medan. The method used in this research was quantitative approach with path analysis with multiple linear regression model assisted by SPSS program version 19. From the results of research conducted, the author conclude that this research yields R-Square on the structural models 1 shows that the variable of celebrity endorser, brand image and customer satisfaction affect the customer loyalty in Medan amounted to 94,4% while 5,6% was explained by other factors. Based on R-Square on the structural models 2 shows that the variable of celebrity endorser and brand image affect the customer satisfaction amounted to 82,7%, while 17,3% was explained by other factors. In the simultaneously test the structural models 1 shows that the variable of celebrity endorser, brand image and customer satisfaction affect the customer loyalty in Medan, this is shown by the value of Fstatistics (537,229) > Ftable (2,31). In the simultaneously test the structural models 2 shows that the variable of celebrity endorser and brand image affect the customer satisfaction, this is shown by the value of Fstatistics (231,602) > Ftable (2,31). In the partially test the structural models 1 shows that the variable of celebrity endorser, brand image and customer satisfaction affect the customer loyalty in Medan. In the partially test the structural models 2 shows that the variable of celebrity endorser and brand image affect the customer satisfaction. The results of significance tests based on the indirect effect shows that there is an indirect effect of the brand image variable on the customer loyalty through the customer satisfaction wiyh significantly.